ASSESSMENT OF THE IMPACTS OF AIR POLLUTION IN SATNA, MADHYA PRADESH: A COMPREHENSIVE ANALYSIS - Bagri, Amit; Sharma, Rama; Vikas Chandra; Kumar, Aditya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This review paper investigates the adverse impacts of air pollution on the environment and public health in Satna, Madhya Pradesh. Satna, an industrial city, has been grappling with escalating levels of air pollutants due to rapid urbanization and industrialization. This paper aims to synthesize existing literature to comprehend the extent of air pollution, its sources, and its consequences on the local ecosystem and human health. Various studies, reports, and data sources are analysed to provide insights into the pollutants prevalent in the region, including particulate matter (PM), sulphur dioxide (SO2), nitrogen dioxide (NO2), and volatile organic compounds (VOCs). Furthermore, the review examines the socio-economic factors contributing to air pollution and evaluates current policies and measures undertaken to mitigate its adverse effects. Recommendations for future research and strategies for effective pollution control and management are also discussed.